THE INFLUENCE OF WORKLOAD, JOB STRESS, AND NON-PHYSICAL WORKING ENVIRONMENT ON TURNOVER INTENTION OF DC WAREHOUSE EMPLOYEES SEMARANG (CASE STUDY PT SUMBER ALFARIA TRIJAYA Branch Semarang) - Handayani, Kristian Tri; Qristin Violinda; Ira Setiawati (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This quantitative research aims to analyze the influence of workload, job stress and nonphysical work environment on turnover intention in warehouse employees at PT Sumber Alfaria Trijaya DC Semarang.The population of this research is warehouse employees with a total of 228 respondents, using the Slovin formula with an error rate of 5%. This research uses a simple random sampling method from probability sampling techniques. This research uses SPSS 26 software measurement analysis tools. The research results show that workload, job stress, and non-physical work environment partially have a negative and significant effect on turnover intention.